2013
DOI: 10.1371/journal.pone.0053251
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Natural Killer Cell Activation and Function during Primary HIV-1 Infection

Abstract: BackgroundRecent reports suggest that Natural Killer (NK) cells may modulate pathogenesis of primary HIV-1 infection. However, HIV dysregulates NK-cell responses. We dissected this bi-directional relationship to understand how HIV impacts NK-cell responses during primary HIV-1 infection.Methodology/Principal FindingsPaired samples from 41 high-risk, initially HIV-uninfected CAPRISA004 participants were analysed prior to HIV acquisition, and during viraemic primary HIV-1 infection. At the time of sampling post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 28 publications
7
43
1
Order By: Relevance
“…While studies in mice have indicated that CD8 ϩ T cells were the crucial effector cells mediating IL-15-induced clearance of tumors (20,60), our results demonstrate that activated NK cells were the crucial effector cells activated by the IL-15 superagonist to inhibit acute HIV-1 infection. The functional activity of NK cells is impaired during chronic HIV-1 infection (9), and it is possible that this impairment may be reversed by treatment with the IL-15 superagonist. Further studies in humanized mice infected with HIV-1 and treated with the IL-15 superagonist should enable us to further delineate the effects of NK cell activation mediated by IL-15 superagonist treatment on inhibiting in vivo HIV-1 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies in mice have indicated that CD8 ϩ T cells were the crucial effector cells mediating IL-15-induced clearance of tumors (20,60), our results demonstrate that activated NK cells were the crucial effector cells activated by the IL-15 superagonist to inhibit acute HIV-1 infection. The functional activity of NK cells is impaired during chronic HIV-1 infection (9), and it is possible that this impairment may be reversed by treatment with the IL-15 superagonist. Further studies in humanized mice infected with HIV-1 and treated with the IL-15 superagonist should enable us to further delineate the effects of NK cell activation mediated by IL-15 superagonist treatment on inhibiting in vivo HIV-1 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Early control of HIV-1 replication can have a beneficial impact on the subsequent disease course, as evidenced by the ability of some individuals whose viremia was suppressed by combination antiretroviral therapy (cART) during acute infection to achieve long-term infection control despite lacking protective HLA-B alleles (5)(6)(7). Prior to the development of an effective HIV-1-specific adaptive immune response, natural killer (NK) cells, crucial innate immune effector cells which are large granular cytotoxic lymphocytes, are rapidly activated and expanded and may contribute to controlling the initial phase of HIV-1 replication (8,9). Infection induces changes in the cellular expression of ligands recognized by NK cell receptors, which enables NK cells to specifically identify and kill virus-infected cells to control and/or abort viral infections prior to the initiation of antigen-specific responses (10).…”
mentioning
confidence: 99%
“…If these cells were derived from the tumor as a result of metastasis, this again would explain the ability of the virus to replicate despite cART, dispersal of virus among tissues, and evidence of rapid and recent expansion of a replicating viral population. Furthermore, cancers can induce type I IFN production, which may play a role in anti-tumor immunity (47), drive T cell dysfunction (48), and contribute to other aspects of HIV disease pathogenesis, for example, virus control (MX2 postentry inhibition [49], APOBEC3 restriction of replication [50], BST-2 virus release [51], and NK cell activation [52]) or immune activation or dysfunction (CD38 expression on CD8 ϩ T cells [53], CD4…”
Section: Discussionmentioning
confidence: 99%
“…However, a direct correlation between NK cell activation and disease progression remains controversial and depends on the patient’s disease state [4851]. Different activation markers have been tested to monitor NK cells in HIV-1 infected patients and one study reported no correlation between NK cell activation and disease progression [49].…”
Section: Nk Cells and Hiv-1 Pathogenesismentioning
confidence: 99%